Bahasa Inggris - Gede Sutrisna; Luh Putu Artini (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2020)
As a typical learning method which is grounded from a scientific approach, problem-based learning (PBL) does not only enhance students’ critical thinking but also helps them actively construct their knowledge and skill. The objectives of this study were to investigate the impact of PBL on (1) students’ speaking skill and (2) their attitude toward ELL. This study employed an embedded mixed-method design which combined one-group pretest-posttest and descriptive qualitative design. It involved a group of 41 students as the sample. The quantitative data were collected through pretest-posttest and questionnaire (closed-ended). Meanwhile, the qualitative data were obtained through observation and open-ended questionnaire. The findings of the study found that students demonstrated better speaking performance after being treated through PBL activities. Besides, they exhibited more positive behavioral, cognitive, and affective attitude toward ELL.